Knowledge, Attitudes, and Practices Regarding Reproductive Health Care Among Adolescents Aged 15–17 Visiting the Hoc Mon District Health Center and Associated Factors in 2025 (Vietnam Journal of Community Medicine, 2026)
Background: Adolescent sexual and reproductive health (SRH) is essential for preventing unintended pregnancy and sexually transmitted infections. Objectives: To describe access to SRH information/services and KAP among adolescents aged 15–17 attending Hoc Mon District Health Center in 2025, and to analyze selected associated factors. Methods: A cross-sectional study was conducted among 218 adolescents selected by convenience sampling from 26 November 2024 to 11 March 2025. Data were collected using a structured questionnaire and analyzed using descriptive statistics, crude odds ratios, 95% confidence intervals and p
Keywords: adolescents; reproductive health; KAP; Vietnam.